Development of a systems-thinking-based assessment instrument for environmental literacy and problem-solving skills in SDG 6 contexts - Leo Muhammad Taufik; Ari Widodo; Hertien Koosbandiah Surtikanti; Taufik Rahman (Education and Development Research, 2026)
This study aims to develop an integrated assessment instrument that measures environmental literacy and problem-solving skills based on system thinking in the context of Sustainable Development Goal (SDG) 6: Clean Water and Sanitation. Using the Borg and Gall R&D framework, the instrument was constructed in five phases involving preliminary analysis, planning, item development, field testing, and revision. The instrument consisted of five contextual essay questions with fourteen sub-indicators aligned to environmental literacy dimensions, systems-thinking components, and Polya’s problem-solving stages. The subjects were 132 tenth-grade high school students enrolled in Biology classes on the topic of Environmental Change from four different schools in Cirebon. The developed instrument consisted of five contextual essay questions with fourteen sub-questions. Content validity was analyzed using Aiken’s V, construct validity using Exploratory Factor Analysis (EFA), and reliability using Cronbach’s Alpha. The results showed an Aiken’s V value of 0.86 (highly valid), KMO value of 0.60, and significant Bartlett’s Test (p < 0.05). Four main factors were identified, consistent with Polya’s problem-solving stages, with a Cronbach’s Alpha of 0.83. The average student score was 61.4, with 2% in the high category, 35% moderate, and 63% low. These results indicate that the developed instrument is feasible to assess students’ environmental literacy and problem-solving skills in the context of tenth-grade Biology learning on Environmental Change related to SDG 6. The overall low student performance suggests that learners have not yet developed a deep understanding of environmental concepts, system interactions, and structured problem-solving processes. This also reveals an instructional gap, particularly in providing opportunities for inquiry-based learning, systems thinking, and contextualized environmental analysis. Therefore, the instrument is valuable for teachers as it not only diagnoses specific weaknesses in students’ competencies but also guides the refinement of instructional strategies to better integrate SDG 6 issues into biology learning.